Management of Injuries of Tendon Achilles at NMC Hospital NawabShah - Saeed Samo; Zulfiqar Soomro; Zamir Soomro; Mehtab Pirwani (Journal of Basic & Applied Sciences, 2012)
Introduction: Tendon Achilles is largest tendon of the body and is made of fibrous tissue, descends from calf & gets attached to calcaneum. The injuries of this strongest tendon are not only uncommon but disabling as well. Twenty one tendons in 20 patients were managed successfully using Bosworth repair in the | department of Orthopaedics NMC Hospital NawabShah during the period from March 2002 to April 2006. Patients & Method: All patients were male and age ranged from 25 years to 55. Thirteen injuries were caused due to direct trauma, 3 patients noticed sudden jerk during high jump while playing, 3 had fall while running on plain ground and use of prolong corticosteroids caused 2 bilateral tendon injuries in one patient (Figure 1). Eleven patients sustained right side injury while 9 had their left side tendon injury. All patients were admitted through OPD & Emergency | departments and were operated after their pre-op work & anesthetist’s fitness was completed. Period lapsed from injury to admission was one day to 3 months and surgery was performed within 1day to 6 days after their admissions (Figure 3). Results: All twenty patients healed completely. Out of these 20 patients 17 were farmers, one medical professional and two were agriculture mechanics (Figure 4). Follow-up period in all these patients was over 15 months and no patient lost to follow- ups. Conclusion: Public awareness service programs and interaction between Orthopaedic consultants and other health professionals including general practitioners of the areas can prevent not only delay in diagnosing such problems, but shall minimize the ailment suffered by these patients. Nevertheless, all injuries of tendon Achilles should be dealt immediately to restore the full function of this strongest tendon of body regardless the lapse of any length of time.